Dizziness and Convergence Insufficiency in Children: Screening and Management - Wiener-Vacher, Sylvette R.; Wiener, Sidney I.; Ajrezo, Layla; Obeid, Rima; Mohamed, Damir; Boizeau, Priscilla; Alberti, Corinne; Bucci, Maria Pia (Frontiers in Integrative Neuroscience, 2019)
Objective In children screened for dizziness with vergence disorders, we tested short and long term efficacy of orthoptic vergence training (OVT) and instructions to reduce screen usage. Methods Prospective study. Of the 179 children referred for vertigo or dizziness (over 3 years) and ophthalmological disorder as the only problem after complete oto-neuro-vestibular testing, 69 presented vergence insufficiency, and 49 accepted to participate to this study. 109 healthy children served as controls. All subjects performed classic orthoptic evaluation and video binocular movement recordings during various oculomotor tasks. Patients were evaluated before OVT (M0), after the end of OVT (M3) and 6 months later (M9). Statistics compared orthoptic and oculomotor parameters between patients and controls over time with one-way ANCOVA, and mixed models, controlling for age and gender. Results Patients reported vertigo that was usually rotatory, lasting <15 min, associated or alternating with headache (50%). Their exposure to small videoscreens and TV was intensive (~3.6 h per day). At M0, all orthoptic and oculomotor parameters were statistically different in patients relative to controls (p<0.0001) except for divergence. At M3, vertigo symptoms had disappeared in all of the patients, and all eye movement parameters improved significantly (p<0.0001). At M9, this improvement remained stable or continued. Conclusion Vergence disorders (assessed by abnormal orthoptic and oculomotor parameters) can generate symptoms of dizziness in children. Orthoptic treatment and instruction to reduce screen usage has a significant and long term effect on vertigo symptoms as well as oculomotor performances. Dizzy children should be screened for vergence disorders.